KONSTRUKSI KECANTIKAN PEREMPUAN DALAM NOVEL GADIS PESISIR KARYA NUNUK Y. KUSMIANA - Insan, Siti Rahma; Supriatna, Agus; Mustopa, Ali (Himpunan Sarjana Kesusastraan Indonesia, Komisariat Sulawesi Tenggara, 2024)
The aim of this research is to represent beauty and to describe the construction of beauty in the novel Pesisir Girl by Nunuk Y. Kusmiana. The method used in this research is qualitative with Naomi Wolf's feminist theory approach. The results of this research show that in the novel Pesisi Girl there is a representation of beauty and the construction of beauty. The representation of beauty is divided into three parts, namely beauty in culture, religion and sex in the coastal communities of Jayapura. The representation of beauty in culture is having white skin and being highly intellectual, religion is being able to maintain purity, and sex is being beautiful who is believed to have sexual qualities. Meanwhile, construction in culture is changing hair styles, wearing make-up, and dressing well. The construction of antiquity in religion is to convey the sanctity that is possessed. Meanwhile, sex does things that affect reproduction.